2010
DOI: 10.1080/15475441003769411
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Syntactic Structure in Children's Sentence Comprehension: Evidence From the Dative

Abstract: Research has demonstrated that young children quickly acquire knowledge of how the structure of their language encodes meaning. However, this work focused on structurally simple transitives. The present studies investigate childrens' comprehension of the double object dative (e.g., I gave him the box) and the prepositional dative (e.g., I gave the box to him). In Study 1, 3-and 4-year-olds correctly preferred a transfer event reading of prepositional datives with novel verbs (e.g., I'm glorping the rabbit to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 42 publications
3
56
1
Order By: Relevance
“…12 The findings of Rowland et al's (2012) priming study suggest that, by 3;8, children's knowledge of the PO-and DO-dative constructions is as abstract as adults', and that young children do not show a lexical boost when the same verb is used in the prime and target sentence. However, this study (unlike Rowland and Noble, 2010) does not address the issue of whether children or adults show better performance when they are potentially able to use a lexical frame such I'm [X]ing the [Y] to [NAME]; indeed, participants hardly ever used pronouns in this study. 13 This study reported a "lexical-boost" effect whereby the youngest children showed priming only when the prime sentence used a slot-and-frame schema -It got [X]ed by it -that could also be used to produce the target sentence.…”
Section: Appendix: the "Weighted Average"mentioning
confidence: 91%
See 1 more Smart Citation
“…12 The findings of Rowland et al's (2012) priming study suggest that, by 3;8, children's knowledge of the PO-and DO-dative constructions is as abstract as adults', and that young children do not show a lexical boost when the same verb is used in the prime and target sentence. However, this study (unlike Rowland and Noble, 2010) does not address the issue of whether children or adults show better performance when they are potentially able to use a lexical frame such I'm [X]ing the [Y] to [NAME]; indeed, participants hardly ever used pronouns in this study. 13 This study reported a "lexical-boost" effect whereby the youngest children showed priming only when the prime sentence used a slot-and-frame schema -It got [X]ed by it -that could also be used to produce the target sentence.…”
Section: Appendix: the "Weighted Average"mentioning
confidence: 91%
“…For example, Conwell and Demuth (2007: Experiment 2) found that novel verbs taught in the PO-dative were extended to the DO-dative only 8% of the time. Exactly as for the transitive construction, Rowland and Noble (2010) found that children showed significantly better (comprehension) performance for prototypical datives that were consistent with possible slot-and-frame patterns (e.g., I'm [X]ing the [Y] to [NAME]). 12 Finally, via this process of gradual abstraction, children arrive at abstract PO-and DO-dative constructions whose slots exhibit probabilistic semantic and -in some cases -phonological properties.…”
Section: [B] [C] [D]mentioning
confidence: 94%
“…Frog; see Rowland & Noble, 2011, for evidence that this solves the problem in an analogous task). Thirty-three English-speaking children took part; fourteen 3-year-olds (mean age = 3;7, range = 2;5 to 4;1) and nineteen 4-year-olds (age = 4;5, range = 4;2 to 4;10).…”
Section: Competing Constructions 15mentioning
confidence: 98%
“…There is some suggestion that the DO-dative appears earlier, though this likely largely reflects the use of semi-productive chunks such as Gimme X. A recent forced-choice comprehension study (Rowland & Noble, 2010) found that 3-4 year-olds demonstrated more robust performance with PO-than DO-datives, but could still correctly interpret DO-dative sentences when given additional cues (e.g., when the recipient was a proper noun). 2.…”
mentioning
confidence: 99%